The Effect on Guided Question Technique on Students’ Writing Skill of Explanation Text at Second Semester (A2) FKIP in Batanghari University Jambi - Kartika Dewi; Siti Aisyah (Universitas Batanghari Jambi, 2023)
The researcher identifies the problem Some students do not know how to develop sentences to a good paragraph writing explanation text and students need of understanding when they lecture clarify Limitation of the Research is areas into a more specific one which focuses on “The effect of Guided Question Technique on Students’ Writing Skill of explanation text at Second Semester (A2) FKIP in Batanghari University Jambi In this research, applied experimental design .In the experimental class, The Population of this research are the students Second Semester (A2) FKIP in Batanghari University Jambi. The population of this research are consists of 13 students includes one class. There is an experimental class which consists of 10 students and as a controlled class which consists 10 students. Data collecting technique was use to find out the research. The researcher use quasi experimental pretest-posttest group design to analyze the data: 1. Pre-Test 2. Post-Test. The data used analyze by students score, normality test, and t-test. Students score. Writing skill explanation text is effect after treatment guided question technique ehich is proven with students' score higher than before treatment. The average pre-test control class 74.23 and post test 76.92. Average pre-test experimental class 93,84 and post-test 95,76. Guided question technique make learning process more interesting. The value of t-test higher than the value of t-table (0.293 > 0.05) based on the finding above, it can be concluded that guided question technique has no significant effect of writing skill.